Effect of Methanolic Extract of Corn Silk on Cisplatin-Induced Nephrotoxicity in Rats: - Zarifi, Farzane; Tanideh, Nader; Zarifi, Fariba; Rafiee, Shima; Khastkhodaei, Maryam; Koohi Hosseinabadi, Omid; Tarkesh, Firoozeh; Kherad, Zahra; Mojahed Taghi, Maryam; Kamali, Mahsa; et al. (Galen Medical Journal, 2018)
Background: Cisplatin is a cytotoxic agent in cancer therapy. Nephrotoxicity is considered as a side effect of cisplatin usage. Using rate models, we studied the possible protective impact of corn-silk (CS) extract against cisplatin-induced nephrotoxicity.MaterialsÂ and Methods: Thirty-five experimental rats were divided into five groups (n=7 per each group) as follow: C1: Control received distilled water only; C2: received one dose of cisplatin, and CS: received 300 mg/kg/day of CS. Both CS1 and CS2 received 200 and 300 mg/kg/day of the CS extract orally, individually, for eight consecutive days. CS1 and CS2 received a single dose of cisplatin on the first day only. The specific biochemical markers and histopathological alterations were evaluated.Result: According to our results, cisplatin administration could have induced severe degeneration in all parts of the nephron tubules and liver. Pre-treatment with CS exhibited a significant decrease in the malondialdehyde (MDA) levels as compared to the values obtained after treatment with cisplatin alone (P<0.01). Moreover, the CS extract with 200 mg dose showed significant (P<0.01) protection against the cisplatin-induced elevation of blood urea nitrogen. Further, the serum levels of alanine transaminase and aspartate transaminase were higher in the cisplatin-treated groups, when compared to the control group (P<0.05). Furthermore, the hepatic function was also improved in cisplatin-treated animals, which were pre-treated with CS.Conclusion: CS has the potential to attenuate nephrotoxicity and lipid peroxidation induced by cisplatin in rats.[GMJ.2018;7:e1258]